A Conceptual Perspective on Brand Switching Behaviour of Consumers in Telecommunication Industry - Abdin, Shahnawaz; Mullick, N. H. (Journal of Commerce and Trade, 2016)
The best thing to happen to mankind was the mobile phone. India has emerged as the fastest growing mobile phone market in the world. Mobile phone was thought of as a magical gadget in the past. It is a reality now. With the advent of advanced technologies like GSM, CDMA, WLL and 3G technology and growing number of service providers, the competition has increased many folds. Every day, companies belonging to both the public sectoras well as the private sector are putting in their resources and efforts to improve their services so as to give maximum benefit to their customers. Hyper competition in the telecommunication industry, availability of number of subscriber options for consumers, diverse tariff rates offered by each player influence consumers to switch their services providers. This paper focuses on enlisting factors influencing consumer switching behaviour in telecommunication industry. However, one thing is certain. By providing value added services and effective pricing strategies; telecom service providers can influence and control to a large extent the consumer brand switching behaviour and can retain customers.